A stylized model of China's growth since 1978 - Linda Glawe; Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2017)
This paper develops a stylized multi-sector growth model of China's economy. We choose a neoclassical modeling approach and focus on the reform process under Deng Xiaoping as China's main growth driver since 1978. Following the literature, we distinguish between three major reform periods, namely the agricultural (1978–1984), the industrial (1984–1992) and the foreign-trade reform period (1992–present). Reflecting the neoclassical view, our model explains China's growth process since 1978 as a sequence of transitory growth phases generated by the reforms. We discuss our model's implications for China's future growth and the middle-income trap as well as growth-stimulating policies in China.
urn:nbn:de:hbz:708-dh9574
Keywords: O10; O11; O40; O41; 330; multi-sector growth modeling; neoclassical growth theory; structural change; China; middle-income trap